Innovative Learning with AR: Experiential LKPD for Electrochemical Cells - Nufus, Gina Hayatun; Abdullah, Abdullah; Rasmiwetti, Rasmiwetti (LAVOISIER: Chemistry Education Journal, 2024)
Learning is the process of interaction between teachers and students in educational institutions which aims to achieve the expected results, through educational interactions and the goals of knowledge, attitudes and skills. Teachers play an important role in learning by providing appropriate teaching materials. Current learning still prioritizes the role of the teacher and students' activities in class do not develop independently through discovery and thought processes. Therefore, to overcome this, learning resources that are integrated with information technology and based on student-centered learning models are needed. One model that can be applied to chemistry learning is the experiential learning model. This research is development research using a 4-D model. The research aims to produce an integrated augmented reality worksheet based on experiential learning on electrochemical cells material. The results of the LKPD validation by material and media validators were considered valid in terms of content suitability, experiential learning characteristic aspects, linguistic aspects, presentation aspects, graphic aspects, appearance aspects, and software utilization aspects with percentages of 98.87%, 100% respectively. , 87.5%, 96.87%, 96.87%, 97.22% and 100%. The results of the user response trials, namely teachers and students, were assessed as good with respective percentages of 97.22% and 92.82%